Asynchronous communication in Java over Infiniband and DECK - Righi, Rd. R.; Navaux, P. O. A.; Cera, M. C.; Pasin, M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Java is becoming an attractive and easy to use programming language. It provides two systems for distributed computing, RMI and sockets, which describe a synchronous communication over TCP/IP. These Java core features may not be the best choice for cluster computing environments, since they do not provide high performance, a critical factor in this scenario. In this paper, presented is the development of Aldeia system, a library proposal to provide asynchronous communication in Java for cluster programming. Aldeia has been deployed on SAN hardware through Infiniband and DECK high-speed substrates. This paper shows the rationale for Aldeia's creation, its structure and encouraging results in synchronous and asynchronous approaches.